Antimicrobial Activity and Phytochemical Screening of Euphorbia helioscopia - WAHEED,K. (2020)
ABSTRACT: Medicinal Plants have been used throughout the world by human beings as a drug and remedies for various diseases since time immemorial. A study was planned to count into the antimicrobial activity and phytochemical screening of Euphorbia helioscopia. The plants were gathered and tested against some standard strains and some human pathogenic microorganisms i.e Escherichia coli, Bacillus Subtilis, Staphylococcus aureus, Klebsiella pneumoniae, Salmonella typhi, Pseudomonas aeruginosa and three fungal strain Trichoderma, R hizopus nigricans, Aspergillus niger. The concentrations of extracting samples (500 and 1,000 mg mL-1) were used against pathogens. Ciprofloxacin was used as positive control in case of bacterial strains and Colfrimazol was used against the fungal strain while dimethyl sulfoxide as negative control. The outcomes indicated that the positive wells potency of Water extract had a 36 mm diameter of zone of inhibition against Escherichia coli and ethanol extract at 1,000 mg mL-1 had maximum (34 mm) zone of inhibition against Bacillus subtilus (36 mm) zone of inhibition against Klebsiella pneumonia and 33 mm of zone of inhibition against Trichoderma harzianum. Likewise, water extract at a concentration of 1,000 mg mL-1 resulted highest value of zone of inhibition (36 mm) against Staphylococcus aureus, a zone of inhibition ( mm) against Salmonella typhi, 36 mm zone of inhibition against Pseudomonas aeruginosa, (32 mm) zone of inhibition against Rhizopus nigricans, a 34 mm zone of inhibition against Acremonium and (34 mm) zone of inhibition against Aspergillus niger. The most susceptible bacteria were K. pneumonia and Bacillus subtilis, while E. coli was the most resistant bacteria and showed zone of inhibition. The ethanolic extract had tannins, lipid, total proteins, carbohydrates, flavonoids, Alkaloid and polyphenolics.